Today Prospects for Tissue Engineering Therapeutic Approach in Dentistry - Maurizio Bossù; Andrea Pacifici; Daniele Carbone; Gianluca Tenore; Gaetano Ierardo; Luciano Pacifici; Antonella Polimeni (The Scientific World Journal)
In dental practice there is an increasing need for predictable therapeutic protocols able to regenerate tissues that, due to inflammatory or traumatic events, may suffer from loss of their function. One of the topics arising major interest in the research applied to regenerative medicine is represented by tissue engineering and, in particular, by stem cells. The study of stem cells in dentistry over the years has shown an exponential increase in literature. Adult mesenchymal stem cells have recently been isolated and characterized from tooth-related tissues and they might represent, in the near future, a new gold standard in the regeneration of all oral tissues. The aim of our review is to provide an overview on the topic reporting the current knowledge for each class of dental stem cells and to identify their potential clinical applications as therapeutic tool in various branches of dentistry.